Wady wrodzoneAscending aortic dissecting aneurysm in child. A case report of successful surgical treatment - Gładki, Marcin; Mroczek, Tomasz; Kordon, Zbigniew; Wójcik, Elżbieta; Składzień, Tomasz; Skalski, Janusz H. (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
An aortic dissecting aneurysm is an acute life-threatening state with a high mortality risk almost equal to 50% in patients without surgical treatment. In children, an aortic dissecting aneurysm is an extremely rare disease. For children and the youth, one of the risk factors of an aortic dissecting aneurysm is a genetic disorder of the connective tissue like Marfan syndrome. An aortic dissecting aneurysm may coexist with a biscupid aortic valve or a complication of hypertension. In this paper, we present a case of a 13-year-old child with an ascending aortic dissecting aneurysm type 1, treated surgically with a good effect.